Effect of Corynebacterium acnes on interferon production in mouse peritoneal exudate cells. - Fischbach, J (1975)
Corynebacterium acnes, an organism closely related to C. parvum, has been recognized to have a striking effect on the reticuloendothelial system, as well as on both humoral and cellular immunity. In mice previously exposed to C. acnes, serum interferon levels induced by injection of Newcastle disease virus (NDV), Chikungunya virus (CV), and polyinosinic-polycytidylic acid are suppressed. When peritoneal macrophages and lymphocytes from animals exposed to C. acnes were cultivated in vitro, their capacity to produce interferon in response to NDV and CV was reduced. Furthermore, the interferon-producing capacity of these cells in tissue culture was inhibited after exposure to C. acnes to vitro. Exposure of separated populations of peritoneal macrophages and lymphocytes to C. acnes in vitro demonstrated that the interferon response to NDV by both cell types is inhibited. Peritoneal macrophages appear to be the major contributor to the interferon response in this system. Finally, this inhibitory effect was shown to occur after exposure to a purified cell wall preparation of C. acnes organisms, as well as a lipid extract of this preparation.